2019
DOI: 10.1186/s13014-019-1416-8
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of cellular communication through tunneling nanotubes in cancer cells and the connection to radiation effects

Abstract: Direct cell-to-cell communication is crucial for the survival of cells in stressful situations such as during or after radiation exposure. This communication can lead to non-targeted effects, where non-treated or non-infected cells show effects induced by signal transduction from non-healthy cells or vice versa. In the last 15 years, tunneling nanotubes (TNTs) were identified as membrane connections between cells which facilitate the transfer of several cargoes and signals. TNTs were identified in various cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 109 publications
(218 reference statements)
0
34
0
Order By: Relevance
“…At least, quite a lot of studies have described that the number of TNT-like structures increased in inflammatory and stress conditions, such as pathogen infections [ 21 , 31 , 65 ], oxidative stress [ 66 ], high intracellular calcium concentrations [ 36 ], inflammatory signals [ 67 , 68 ], misfolded proteins, and pathogenic amyloid aggregates [ 8 , 42 , 69 , 70 ]. Moreover, the tumor microenvironment (hypoxia, acidic pH, hyperglycemia, and serum deprivation), as well as chemo- and radiotherapy-induced reactive oxygen species (ROS) production, leads to more TNTs in tumor cells [ 39 , 66 , 71 , 72 , 73 , 74 , 75 , 76 ]. Additionally, exosomes derived from malignant cells or vesicle recycling induce an increased rate in the formation of TNTs [ 46 , 77 ].…”
Section: Tnts Are Heterogeneous Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…At least, quite a lot of studies have described that the number of TNT-like structures increased in inflammatory and stress conditions, such as pathogen infections [ 21 , 31 , 65 ], oxidative stress [ 66 ], high intracellular calcium concentrations [ 36 ], inflammatory signals [ 67 , 68 ], misfolded proteins, and pathogenic amyloid aggregates [ 8 , 42 , 69 , 70 ]. Moreover, the tumor microenvironment (hypoxia, acidic pH, hyperglycemia, and serum deprivation), as well as chemo- and radiotherapy-induced reactive oxygen species (ROS) production, leads to more TNTs in tumor cells [ 39 , 66 , 71 , 72 , 73 , 74 , 75 , 76 ]. Additionally, exosomes derived from malignant cells or vesicle recycling induce an increased rate in the formation of TNTs [ 46 , 77 ].…”
Section: Tnts Are Heterogeneous Structuresmentioning
confidence: 99%
“…During the past few years, various studies have suggested TNTs as a potential target for the treatment of tissue injury, tumor drug resistance, and infection ( Table 1 ). As discussed earlier, stressed tumor cells adaptively respond to the tumor microenvironment or therapeutic stress by forming more TNTs [ 28 , 72 , 104 , 105 ]. Oncogenes including K-RAS and P53 participate in the activation of proteins regulating the actin cytoskeleton [ 39 , 73 ].…”
Section: Tnts As Potential Therapeutic Targetsmentioning
confidence: 99%
“…In both cases, cell-to-cell communication directly influences the biological effects to the tissue and therefore to the organism caused by radiative stress. The underlying mechanism as well as the question of to what extend cellular communication affects the cell survival and genetic alterations after irradiation remain obscure (17). During evolution, cells developed several approaches to communicate.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 7 , cell-to-cell transfer via TNTs can be inhibited by TNT downregulation by compounds such as cytarabine, NF-κB inhibitors, and cytochalasin B or latrunculin B [ 164 , 165 ]. The production and release of extracellular vesicles can be inhibited in various cell types by diverse compounds, including calcium channel blockers, ROCK (rho-associated protein kinase) inhibitors, calpain inhibitors, PKC inhibitors, methyl-β-cyclodextrin, chlorpromazine, and the vitamin B5 derivative pantethine [ 111 , 166 ].…”
Section: Novel Intrinsic Mechanisms Of Active Drug Extrusion At Thmentioning
confidence: 99%